PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN PULP DAN KERTAS DI BURSA EFEK INDONEISA - Faizaturrahmi, Faizaturrahmi; Handajani, Lilik (COMPETITIVE, 2024)
This study aims to analyze the impact of financial variables such as Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA), Total Assets Turnover (TAT), and Earnings Per Share (EPS) on the stock returns of companies. The analysis is conducted using historical data from manufacturing companies listed on the stock market. The results of the study indicate that the Current Ratio (CR) and Debt to Equity Ratio (DER) do not have a significant influence on stock returns, while Return On Assets (ROA) has a positive and significant impact. The Total Assets Turnover (TAT) variable has a negative but not significant effect, whereas Earnings Per Share (EPS) has a positive and significant influence on stock returns. For investors, it is recommended to consider various financial and operational factors holistically when making investment decisions. While ROA and EPS have shown to positively influence stock returns, relying solely on these indicators may not be sufficient. It is crucial for investors to also take into account the overall financial health and operational efficiency of the company, market conditions, and other external factors that may affect the company’s performance. Diversifying investments and regularly monitoring financial metrics can also help in mitigating risks and enhancing the potential for higher returns. In conclusion, this study underscores the importance of comprehensive financial analysis in investment decision-making. By understanding and evaluating multiple financial variables, investors can make more informed and strategic choices, ultimately leading to better investment outcomes.